PROCESS FOR RECOVERING METALS FROM Li-CONTAINING STARTING MATERIAL

JP2025022894AActive Publication Date: 2025-02-14UMICORE(BE)
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2024189994
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-04-19
Filing Date
2024-10-29
Publication Date
2025-02-14
Estimated Expiration
2040-04-17

AI Technical Summary

Benefits of technology

、塩化物又は硝酸塩マトリックスにおいて見られる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025022894000001_ABST
    Figure 2025022894000001_ABST
Patent Text Reader

Abstract

To provide a process for recovering metals such as Ni and Co from a Li-containing starting material.SOLUTION: In particular, this process relates to a process for recovering metals M comprising Ni and Co from a Li-containing starting material, comprising the steps of: Step 1: preparing the starting material, comprising Li-ion batteries or their derived products; Step 2: removing Li in an amount of more than the maximum of (1) 30% of the Li present in the starting material, and (2) a percentage of the Li present in the starting material determined to obtain a Li:M ratio of less than 0.70 in a subsequent acidic leaching step; Step 3: executing subsequent leaching using relative amounts of Li-depleted product and a mineral acid, thereby obtaining a Ni-and Co-bearing solution; and, Step 4: executing crystallization of Ni, Co, and optionally Mn. Due to lower reagent consumption and higher Ni and / or Co concentration during hydrometallurgical processing, the invention is an efficient and economic process for the production of crystals suitable for battery material production.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for recovering metals from Ni- and Co-containing starting materials and subsequently producing battery precursors for use in lithium-ion rechargeable batteries. [Background technology]

[0002] One common battery chemistry includes a cathode powder containing metallic lithium, nickel, manganese, and cobalt (NMC). Another commonly used chemistry utilizes a cathode powder containing lithium, nickel, cobalt, and aluminum (NCA).

[0003] During the life cycle of a lithium-ion battery, various waste materials are generated that need to be recycled to comply with environmental regulations and laws. Already during the battery manufacturing process, manufacturing waste is generated due to the difficulty of meeting quality standards. Such materials range from cathode powders, electrode foils, separator foils, to completed battery cells or modules.

[0004] In addition to the manufacturing waste, end-of-life batteries also need to be recycled. This results in an even more complex waste stream that mainly includes lithium batteries with all their components along with electrical or electronic components, but also potentially non-lithium batteries such as nickel-cadmium batteries, nickel-metal-hydride batteries, and zinc batteries. These manufacturing wastes and derivatives of end-of-life batteries are also available for recycling in the form of powder or black chunks, which are the result of mechanical and / or thermal pretreatment.

[0005] The chemical complexity of scrap materials increases towards the end of the manufacturing process as more and more components are added to the product, so battery cells and modules may contain a vast number of different elements, such as Ni, Co, Mn, Li, Fe, Al, V, P, F, C, Ti, and Mg in the cathode, Li, Ti, Si, C, Al, and Cu in the anode, Li, F, P, and volatile organic compounds in the electrolyte, and Al, Fe, Cu, Ni, Cr, and plastics containing Cl and Br in the casing.

[0006] The amount of used batteries is expected to exceed 100,000 tonnes per year over the next decade, mainly due to the ongoing electrification of the automotive industry, and battery recycling businesses are set to grow accordingly.

[0007] One conventional method uses solvent extraction to extract Co and Ni from the purified leach solution containing Li. In another such method, Co and Ni are separated from the leach solution by precipitation, resulting in a Li-containing stream that is also depleted in Ni and Co. The Li in the solution after metal extraction or precipitation is typically 2 CO 3 Salt or Li 3 PO 4 The metals are removed from the solution as salts. Meshram et al. [Hydrometallurgy, Vol. 150, pp. 192-208, 2014] provide an overview of conventional methods for recovering metals from spent batteries. These methods have the disadvantage of consuming a base such as NaOH in excess of the stoichiometric amounts relative to Ni and Co, and require the use of a stoichiometric amount of Na relative to Li to obtain a Li concentrate. 2 CO 3 Or Na 3 PO 4 is consumed.

[0008] Another method is known from CN108439438, in which calcined lithium-containing battery waste is acid-leached to obtain a solution containing Li, Co, Ni, Mn, Al, Fe and Cu, from which Cu, Fe and Al are first removed, then Li is removed by extraction using an extractant, followed by crystallization of mixed Ni, Co, Mn sulfates.Such a method is also known from CN107768763, in which battery waste is acid-leached, then Cu, Fe and Al are removed from the resulting solution by precipitation, then Li is removed as LiF, followed by crystallization of mixed Ni, Co, Mn sulfates.

[0009] However, these known methods involve the synthesis of, for example, NiSO in the presence of dissolved Li. 4 A drawback of this approach is that the solubility of Ni in Ni is greatly reduced, which means that processing equipment such as reactors at recycling plants can only hold a limited amount of Ni at a given volume, limiting the Ni production capacity of the equipment.

[0010] In such known methods, a significant amount of acid is consumed to dissolve the contained Li. This can easily amount to 33% of the total acid consumption in a typical battery waste. Further agents are then used to remove the Li. The dissolution and removal of Li therefore results in the discharge of further salts.

[0011] Also, extraction processes are expensive because they usually require expensive extractants as well as additional steps such as loading the metal(s) to be removed onto the extractant and removing the extractant.

[0012] For economic and environmental reasons it is therefore necessary to achieve higher Ni concentrations in the leach solution than are possible with these known methods, whilst preferably also consuming less acid in the dissolution, less or no consumption of chemicals in the removal of Li from the leach solution and therefore less discharge of salts. [Prior art documents] [Patent documents]

[0013] [Patent Document 1] Chinese Patent No. 108439438 [Patent Document 2] Chinese Patent No. 107768763 [Non-patent literature]

[0014] [Non-Patent Document 1] Meshram et al., Hydrometallurgy, vol. 150, pp. 192-208, 2014. Summary of the Invention [Problem to be solved by the invention]

[0015] It is therefore an object of the present invention to provide a method for recovering the metal M (wherein M represents Ni and Co, and optionally Mn) from starting materials containing Li-ion batteries or their derivatives, which has the advantage of allowing a higher concentration of M to be achieved in the leach solution, reducing the consumption of chemicals. [Means for solving the problem]

[0016] This object is achieved by providing a method according to claim 1, in particular by at least partially removing Li from the starting material. In order to reach higher metal concentrations, such as higher concentrations of Ni, in a given volume and to maintain them during subsequent processing steps, it is essential to partially or completely remove Li before leaching Ni and Co. This allows for a reduction in chemical consumption as well as an improved throughput of the processing equipment.

[0017] The present invention therefore relates to a method for recovering metals M, including Ni and Co, from a Li-containing starting material, comprising the steps of: Step 1: Providing starting materials comprising a lithium ion battery or a derivative thereof; Step 2: - a pyrometallurgical refining process using a slag-forming agent to produce one or more of a Li-bearing slag phase and Li-fumes, and a Li-reduced Ni-Co bearing phase that is susceptible to acid leaching; - a heat treatment process using a reducing agent to produce a Ni-Co-bearing residue containing at least one water-soluble Li-compound and selectively remove said at least one Li-compound by washing with an aqueous solution, thereby obtaining a Li-reduced Ni-Co-bearing residue susceptible to acid leaching; - hydrometallurgical leaching using aqueous or acidic solutions to selectively leach Li from the starting material, Ni and Co being at least partially insoluble, and solid-liquid separation to obtain a Li-depleted Ni-Co-bearing residue that is amenable to acid leaching; removing Li in excess of the maximum of: (1) 30% of the Li present in the starting material; and (2) a percentage of Li present in the starting material determined to obtain a Li:M ratio of 0.70 or less in a subsequent acid leaching step; Step 3: carrying out a subsequent leaching using relative amounts of the Li-depleted Ni-Co-bearing material obtained in step 2 and a mineral acid, thereby obtaining a Ni- and Co-bearing solution; Step 4: Crystallizing Ni, Co, and optionally Mn; The present invention relates to a method comprising the steps of:

[0018] In industrial plants, the starting material for a process is sometimes called the "feed" or "metallurgical charge", especially when talking about metallurgical processes such as smelting or metal refining.

[0019] The derived products can include any kind of product scrap from different stages of battery production, black mass, electrode foils, end-of-life batteries, or modules. Lithium-ion batteries refer to batteries that use Li as their charge carrier, including the various battery types currently on the market, as well as upcoming new battery technologies such as, but not limited to, solid-state batteries.

[0020] The Li:M ratio is the molar concentration of Li to the total molar concentration of metal M, where M is the total molar concentration of Ni+Co+Mn.

[0021] FIG. 1 shows how the Li:M ratio obtained in step 3 varies as a function of different Li removal rates obtained in step 2 for three different battery scraps: Al- and Cu-free battery scrap (circles); battery scrap with low Al and Cu contents (squares); and battery scrap with high Al and Cu contents (triangles).

[0022] Decreasing the Li:M ratio increases the solubility of, for example, Ni. The solubility of a metal such as Ni is much higher in the absence of dissolved Li than in the presence of Li. This is due to the increased concentration of the corresponding anion, such as sulfate, in the presence of Li. Figure 2 shows the relationship between the solubility of Ni and the solubility of Li. 2 SO 4 and NiSO 4 This shows the solubility of Ni as a function of the Li:M ratio for solutions containing NiSO 4 and Li 2 SO 4 This confirms that the solubility of Ni decreases with increasing Li:M ratio in the case of solutions containing only Li.

[0023] As with metal sulfates, the same considerations are applicable to other inorganic metal salts such as nitrates, chlorides, and mixtures thereof, where the metals may be Ni, Co, Mn, Fe, Cu, Al, and others.

[0024] It is noted that step 2 of the process defines two criteria (1) and (2) that are applied to the amount of Li to be removed, and the higher of the two is then selected. Criterion (1) is in principle valid for all starting materials, but criterion (2), i.e. removal of Li to obtain a Li:M ratio of 0.70 or less in a subsequent acid leaching step, may be preferred for starting materials having a Li:M ratio of more than 0.70 in the original starting material.

[0025] A Li:M ratio of 0.70 or less is considered appropriate in an industrial plant for economic reasons, since it significantly increases the production capacity of the plant (compared to conventional processes using the same volume). A Li:M ratio of 0.70 or less corresponds to a metal concentration (excluding Li) of 120 g / L or more (in the sulfate matrix) in the subsequent leaching step 3 of the present invention. Especially in the crystallization step 4, high metal concentrations are beneficial.

[0026] In another embodiment, the Li:M ratio in step 2, criterion (2), is 0.50 or less. It is advantageous in this process to have a metal concentration of 128 g / L or more (in the sulfate matrix), which corresponds to a Li:M ratio of 0.50 or less. By removing Li in step 2 of the process, such lower Li:M ratios are obtained in the leach solution.

[0027] In another embodiment, steps 1 and 2 of the above method are as follows: 1. A method for recovering metals M, including Ni and Co, from Li-containing starting materials, including lithium ion batteries or their derivatives, comprising: Step 1: Providing said starting material having a Li:M ratio greater than 0.50; Step 2: - a pyrometallurgical refining process using a slag-forming agent to produce one or more of a Li-bearing slag phase and Li-fumes, and a Li-reduced Ni-Co-bearing phase that is susceptible to acid leaching; - a heat treatment process using a reducing agent to produce a Ni-Co-bearing residue containing at least one water-soluble Li-compound and selectively remove said at least one Li-compound by washing with an aqueous solution, thereby obtaining a Li-reduced Ni-Co-bearing residue susceptible to acid leaching; - hydrometallurgical leaching using aqueous or acidic solutions to selectively leach Li from the starting material, Ni and Co being at least partially insoluble, and solid-liquid separation to obtain a Li-depleted Ni-Co-bearing residue that is amenable to acid leaching; removing a percentage of Li present in said starting material determined to obtain a Li:M ratio of 0.50 or less in a subsequent acid leaching step by using one or more of The method includes:

[0028] However, it is more preferred to remove even more Li in step 2 of the process as this will reduce the Li:M ratio even further and increase the beneficial effects in the subsequent leaching step 3. Thus, in another embodiment, the metal concentration is 135 g / L or more (in the sulfate matrix), which corresponds to a Li:M ratio of 0.30 or less, more preferably 139 g / L or more (in the sulfate matrix), which corresponds to a Li:M ratio of 0.20 or less. Similar beneficial effects as described for the sulfate matrix are seen in chloride or nitrate matrices.

[0029] Decreasing the Li:M ratio to 0.50 or less, preferably 0.30 or less, more preferably 0.20 or less, is advantageous in crystallization step 4 of the present invention, since it allows producing pure crystals, i.e. crystals that are not contaminated with Li. Obtaining purer Ni- and / or Co-crystals is advantageous for producing, for example, positive electrode active materials, possibly avoiding further process or purification steps.

[0030] Furthermore, if Li is removed prior to the leaching step, the consumption of chemicals is significantly less. For example, the consumption of acid in step 3 of the process is already 5% less if approximately 30% of the Li in the starting material is removed in step 2.

[0031] In another embodiment, the heat treatment process of step 2 is carried out at a temperature above 250° C. A variety of reducing agents can be used in the heat treatment process, including but not limited to metal powders, anode materials, sulfur, carbon, CO, CO 2 , C.H. 4 , H 2 S, SO 2 , NaHSO 4 , or H 2The negative electrode material may function as a reducing agent.

[0032] In another embodiment, the step of selectively removing at least one water-soluble Li-compound by washing with an aqueous solution is carried out at a pH of 2.5 or higher. By selectively removing is meant selective towards Ni and Co.

[0033] In another embodiment of this method, the water soluble Li-compound in step 2 is Li 2 O, Li 2 CO 3 , LiHCO 3 , LiCl, Li 2 SO 4 , LiF, LiOH, or one or more of the following: The respective counter ions to Li may come from the various possible types of starting materials used in the recycling process, or from added reducing agents.

[0034] In another embodiment of this process, the pyrometallurgically refined Ni-Co-bearing phase of step 2 is ground to a particle size distribution having an average diameter of 10 mm or less, preferably 1 mm or less, more preferably 0.5 mm or less, which is advantageous for efficient and rapid leaching in step 3. The grinding to such an average particle size distribution is carried out by standard methods known to those skilled in the art, such as granulation, atomization, or milling.

[0035] In another embodiment, step 2 can be performed using a hydrometallurgical process that selectively leaches out lithium by operating under strict control of specific pH, temperature, and redox potential. Selective dissolution can be performed with water, called selective washing, or with the addition of specific leaching agents, such as but not limited to phosphoric acid or oxalic acid, or in the presence of oxidizing agents, such as but not limited to persulfates, ozone, chlorine, etc. Other hydrothermal processes expose the battery scrap to high temperatures, e.g., >80° C., that exceed normal leaching conditions, or use mechanical energy, such as but not limited to wet grinding, to liberate lithium into soluble Li salts.

[0036] In a preferred embodiment, the mineral acid is HNO 3 , H 2 SO 4 and HCl.

[0037] For economic reasons, the Li-depleted Ni- and Co-bearing solution after step 3 of the process preferably contains at least 35%, more preferably at least 50%, more preferably at least 75%, most preferably at least 90% or more of the Ni and Co present in the starting material. One or more by-products containing the remaining portion of Ni and Co are then also obtained, which can be subjected to further recycling processes.

[0038] The leaching rate in step 3 can be optimized by adding reducing or oxidizing agents. Reducing agents that can be used in step 3 include, but are not limited to, sulfide components, sulfur, sulfur dioxide, sulfite components, hydrogen peroxide, metal compounds, and hydrogen. Oxidizing agents that can be used in step 3 include, but are not limited to, persulfates, oxygen, hydrogen peroxide, chlorine, and ozone.

[0039] Optionally, step 3 can be carried out under specific conditions, with controlled pH and redox potential, and / or using specific reagents, which minimizes the dissolution of impurities such as Mn, Fe, Cu, Al, etc. This is a clear advantage of this step, as it increases the concentration of Ni and Co in the Ni- and Co-bearing solutions after leaching.

[0040] One such method to avoid dissolution of Cu is obtained by controlling the redox potential of the acidic solution vs. Ag / AgCl below 200 mV and maintaining the pH of the acidic solution below 4. In another such method, Co and Ni are selectively leached from Cu in the presence of a sulfur-containing agent, which results in a Co- and Ni-bearing solution and a leach residue containing Cu.

[0041] In another embodiment, the method includes a purification step between steps 3 and 4, where the Ni- and Co-bearing solution from step 3 also contains Cu and / or Fe and / or Al, and where in the purification step Cu and / or Fe and / or Al are removed from the Ni- and Co-bearing solution. The removal of one or more of the impurities can be performed prior to the solid-liquid separation of step 3.

[0042] The removal of Fe is preferably performed by O 2 Or H 2 O 2 As an oxidizing agent, Fe 3+ This can be addressed by subjecting the solution to oxidizing conditions so as to precipitate the compound.

[0043] Cu removal can be accomplished by standard methods known to those skilled in the art, such as cementation or ion exchange.

[0044] Al can also be removed by standard methods known to those skilled in the art, such as solvent extraction or hydrolysis.

[0045] In another embodiment, the Ni- and Co-bearing solution from step 3 also contains Mn, and the method includes a Mn removal step between steps 3 and 4, where Mn is removed from the Ni- and Co-bearing solution. Mn can be removed, for example, by solvent extraction or by addition of Mn. 4+ The compounds can be removed from such Ni- and Co-bearing solutions by oxidative precipitation.

[0046] In another embodiment, step 4 is carried out by lowering the temperature of the Ni- and Co-bearing solution, and / or by removing water from the Ni- and Co-bearing solution, and / or by solvent displacement crystallization. It is noted that the crystallization in step 4 includes simultaneous co-crystallization of Ni-compounds and Co-compounds, simultaneous co-crystallization of Ni-compounds, Co-compounds and Mn-compounds, respectively.

[0047] Preferably, the method does not include a solvent extraction or ion exchange step to extract Ni and / or Co from the Ni- and Co-bearing solution. This is in contrast to the previously used methods to extract Ni and / or Co from the Ni- and Co-bearing solution by specifically applying said method to obtain sufficiently pure Co-salt and / or Ni-salt. The advantage of this method is therefore that it does not require expensive chemicals such as ion exchange solids or solvents for solvent extraction, as well as their stripping agents, compared to the methods of extracting the majority of the metals, which extract the desired elements Ni and Co, and optionally Mn, from the solution. On the other hand, it is still always possible to add a purification step before the final crystallization step to remove certain metals from the Ni- and Co-bearing solution. For example, if the aim is to produce pure nickel crystals, cobalt can be removed before crystallization.

[0048] As an additional advantage, the crystallization step, step 4, provides a purification step for trace impurities still present in the solution after step 3 and possible purification steps. Furthermore, crystallization also provides a purification step towards residual Li. At low Li:M ratios, Li preferably goes into liquid solution during crystallization of Ni and / or Co. Residual Li is Li that is not removed during step 2 and thus may be present in the Ni- and Co-bearing solution obtained in step 3.

[0049] In another embodiment, prior to step 4 of this method, the ratio of Ni to Co in the Ni- and Co-bearing solution is adjusted to a desired value by adding Ni and / or Co in dissolved form or as one or more compounds that are soluble in the Ni- and Co-bearing solution. In this manner, a crystallized product can be created that already has the desired Ni to Co ratio for the particular cathode active material selected, potentially avoiding further process or purification steps in the manufacture of those materials.

[0050] In another embodiment, prior to step 4 of this method, the ratio of Ni to Co to Mn in the Ni- and Co-bearing solution is adjusted to a desired value by adding one or more of Ni, Co, and Mn in dissolved form or as one or more compounds that are soluble in the Ni- and Co-bearing solution. In this manner, a crystallized product can be created that already has the desired Ni to Co to Mn ratio for the particular cathode active material selected, potentially avoiding further process or purification steps in the manufacture of those materials.

[0051] The presence of Mn in the starting materials is optional: considering the low cost and availability of suitable Mn-containing chemicals, even Mn-free Ni- and Co-bearing solutions can be used to prepare precursors of active materials for Ni-Co-Mn-containing batteries with the later addition of a Mn source.

[0052] In another embodiment, the Ni- and Co-bearing solution contains more Ni than Co when expressed in g / l.

[0053] In another embodiment, the Ni- and Co-bearing solution contains more Ni than the sum of Co and Mn, expressed in g / l.

[0054] In another embodiment, the method includes a purification step between steps 3 and 4, where Co is selectively removed from the Ni- and Co-bearing solution to obtain a Co-reduced Ni-bearing solution suitable for obtaining Ni crystals.

[0055] In another embodiment of this method, the starting material contains Ni, Co, Li, Al, F, and one or more of Cu and Fe, and the pyrometallurgical refining process of step 2 is a reduction refining of the starting material using a flux, and the Ni-Co bearing phase is an alloy containing a majority of Ni, Co, Cu and at least a portion of Fe, and the alloy is depleted in Li, Al, and F.

[0056] By majority is meant at least 50%, preferably 75%, and more preferably 90% or more of the total amount of Ni, Co, and Cu present in the starting material. [Brief description of the drawings]

[0057] [Figure 1] FIG. 13 shows how the Li:M ratio obtained in step 3 varies as a function of different Li removal rates obtained in step 2. [Diagram 2] FIG. 1 shows the solubility of Ni as a function of the Li:M ratio. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0058] In the drawings and the following detailed description, preferred embodiments are described in detail to enable the practice of the invention. Although the invention is described with reference to these specific preferred embodiments, it will be understood that the invention is not limited to these preferred embodiments. To the contrary, however, the invention includes numerous alternatives, modifications, and equivalents, as will become apparent from a consideration of the following detailed description. The invention is further illustrated in the following examples. EXAMPLES

[0059] The end-of-life batteries are recycled in 60 liter alumina crucibles. The end-of-life batteries contain 10 wt% Al, 2 wt% Fe, 4 wt% Mn, 4 wt% Co, 9 wt% Cu, 13 wt% Ni, 2.5 wt% Li, and 25 wt% C. The remainder includes elements such as hydrogen, oxygen, and fluorine.

[0060] The starting slag is heated to a temperature of 1450°C using an induction furnace. Once this temperature is reached, the mixture of dead batteries and flux is gradually added to the liquid slag over a period of 2 hours. During this time, 50 kg of batteries are added along with 10 kg of limestone and 5 kg of sand. For the starting materials with dead batteries, starting slag, and flux as described, the Li:M ratio is 1.53. During the charging of the feed, O 2is blown above the bath at a rate of 220 L / h to burn off any metallic Al and carbon in the cells. After the last addition, CO is blown through the bath at a rate of 300 L / h for 1 h to obtain the desired degree of reduction, thereby forming slag and alloy phases. The samples are removed from the slag and, after cooling, the alloy and the phases are separated. The composition of the resulting phases is given in Table 1.1, the remaining part of the mass being fumes. The removal rate of Li during this pyrometallurgical refining process is 100%.

[0061] [Table 1]

[0062] The alloy phase fraction resulting from the smelting operation is remelted under an inert atmosphere and atomized in a water jet, which results in a powder fraction with an average grain size of 0.2 mm.

[0063] 600 g of the atomized powder is added to a glass beaker containing 3.2 L of water. An agitator is used to suspend the powder and sparge with oxygen gas which is injected into the bottom of the beaker. The oxygen acts as an oxidant during leaching. The mixture is heated and maintained at 80°C. 1.05 L of 998 g / L sulfuric acid is fed to dissolve the powder for 8 hours. After 9 hours the leaching process is complete with essentially all the metals dissolved at this stage. The beaker is cooled and the contents are filtered. The resulting leach filtrate volume is 4.05 L and contains 60 g / L Ni, 19 g / L Co, 8.0 g / L Mn, 38 g / L Cu, 9.1 g / L Fe, <0.1 g / L Al with a Li:M ratio of 0.

[0064] Cu is then selectively removed from the solution by cementation with Ni powder. This is done by slowly pumping the leach solution into another heated and stirred beaker while simultaneously adding 184 g of metallic Ni powder to the same beaker. During this process, Ni is exchanged with Cu in the solution. After filtration, a Cu-Ni mixed cement and a copper-free solution are obtained.

[0065] In the next step, the Fe is removed by precipitating it as a hydroxide. This is done by reheating the copper-removed solution to 80 °C. Oxygen gas is injected into a stirred beaker and 135 g of NiCO 3 is added for 3 hours. Under these conditions, Fe(OH) 3 After filtration, an iron-rich cake and 3.9 L of filtrate are obtained, which contains 108 g / L Ni, 18 g / L Co, 7.7 g / L Mn, <0.01 g / L Cu, <0.01 g / L Fe, <0.1 g / L Al.

[0066] The concentrations of Co, Mn, and Ni are then corrected to obtain the desired Ni to Co to Mn ratio before the final crystallization of the Ni-Co-Mn mixed sulfate. In this example, we target a Ni:Co:Mn molar ratio of 6:2:2. This is achieved by reheating the solution in a stirred beaker at 80°C and adding 323 g of cobalt sulfate heptahydrate and 336 g of manganese sulfate monohydrate crystals. 1.3 L of water is also added at this stage to obtain a filtrate containing 80 g / L Ni, 27 g / L Co, 26 g / L Mn, <0.01 g / L Cu, <0.01 g / L Fe, <0.1 g / L Al.

[0067] Evaporative crystallization is carried out at 45°C under vacuum. At the end of the crystallization process, mixed sulfate crystals of nickel, cobalt and manganese are obtained. The crystals contain 16.1% Ni, 4.6% Co, 3.5% Mn, <0.002% Cu, <0.002% Fe, <0.002% Al. The remainder consists of sulfates and water of hydration. EXAMPLES

[0068] To remove Li prior to leaching, mechanically pretreated cathode foil manufacturing waste, called black agglomerate, is first thermally pretreated in the presence of reducing agent C. The black agglomerate contains 33% Ni, 11% Co, 10% Mn, <0.1% Cu, <0.1% Fe, 0.4% Al, 6.1% Li. The remainder includes elements such as oxygen, carbon, and fluorine. The Li:M ratio of the starting material is 0.94.

[0069] 300 g of black mass, a mechanically pretreated cathode foil manufacturing waste material having the above composition, was mixed with 15.6 g of carbon and 244.8 g of CaCl 2 2H 2 The mixture is placed in a tray and the furnace is heated to N 2 The mixture is heated in an electric furnace to a temperature of 700° C. while constantly purging with water. The temperature of 700° C. is maintained for 6 hours. Over this time, the oxides of Ni, Mn, and Co are (partially) reduced to give water-soluble Li salts, i.e., Li 2 CO 3 and / or LiCl are formed. After 6 hours, the furnace containing the mixture is cooled to room temperature with N 2 Cool under atmosphere.

[0070] 350 g of the resulting mixture are added to a glass beaker containing 1 L of water. A stirrer is used to suspend the powder. The mixture is heated and maintained at 80°C. 32 mL of sulfuric acid (970 g / L) are slowly fed over 3 h to optimize the dissolution of Li. After 5 h, the beaker is cooled and the contents are filtered. At the end of pyrolysis and washing, 261 g of concentrate containing Ni, Co, and Mn and 1.3 L of Li filtrate are obtained. The mass balance of this pretreatment operation is shown in Table 2.1. 88% of the Li is removed during this step.

[0071] [Table 2]

[0072] 261 g of Ni, Mn, Co concentrate are then added to a glass beaker containing 0.8 L of water. A stirrer is used to suspend the powder. The mixture is heated and maintained at 80°C. 241 mL of sulfuric acid (998 g / L) is slowly fed over 3 hours to dissolve the powder. At the end of the leaching, 56 mL of 35% hydrogen peroxide is added as a reducing agent. After a total of 4 hours, the leaching process is completed, with essentially all the metals dissolved at this stage. The beaker is cooled and the contents are filtered. 1.02 L of leach filtrate is obtained, the solution contains 76 g / L Ni, 25 g / L Co, 23 g / L Mn, <0.01 g / L Cu, <0.01 g / L Fe, 0.7 g / L Al, 1.5 g / L Li, with a Li:M ratio of 0.10.

[0073] The pH of the filtrate is then increased to selectively remove Al from the solution. First, the leach filtrate is placed in a heated glass beaker and maintained at 80 °C. A stirrer is used to ensure a homogeneous solution. 8.5 g of CoCO 3 is added to the leach solution. After 3 hours, Al is removed from the solution to very low levels and the contents are filtered. The purified solution contains 76 g / L Ni, 27 g / L Co, 23 g / L Mn, <0.05 g / L Cu, <0.05 g / L Fe, <0.05 g / L Al, and 1.5 g / L Li.

[0074] Evaporative crystallization is carried out at 60°C. As a result, mixed sulfate crystals of nickel, cobalt, and manganese are formed. The crystals contain 15.7% Ni, 5.2% Co, 2.3% Mn, <0.002% Cu, <0.002% Fe, <0.002% Al, <0.01% Li. The remainder consists of sulfates and water of hydration. EXAMPLES

[0075] 200 g of Nickel-Cobalt-Aluminium (NCA) cathode manufacturing scrap is processed. The manufacturing scrap contains 48% Ni, 9% Co, <0.1% Mn, 2% Al, 7% Li. The remainder contains elements such as oxygen. The Li:M ratio of the starting material is 1.04.

[0076] 200 g of cathode production scraps are added to a 2 L reactor containing 1 L of water. The mixture is stirred and heated on a hot plate to a temperature of 80 °C. 220 mL of sulfuric acid with a concentration of 987 g / L are added for 6 h. Under such conditions, Li dissolves, while trivalent Co and Ni do not. After 6 h, the solid-liquid mixture is filtered on a Büchner filter. Approximately 1.1 L of filtrate is collected. By this operation, most of the lithium is leached and is present in the filtrate. 107 g of Li-reduced residue is obtained, which is rich in Ni and Co. The composition of the filtrate and the residue after drying can be seen in Table 3.1. The removal rate of Li is more than 99% in the selective Li leaching process.

[0077] [Table 3]

[0078] The Ni-Co concentrate is added to a glass beaker containing 0.4 L of water. A stirrer is used to suspend the powder. The mixture is heated and maintained at 80°C. 130 mL of concentrated sulfuric acid (998 g / L) is slowly fed to dissolve the powder. 77 mL of 35% hydrogen peroxide is added as a reducing agent during the leaching. After 8 hours, the leaching process is completed. The beaker is cooled and the contents are filtered. The leach solution (550 mL) contains 102 g / L Ni, 19 g / L Co, <0.05 g / L Mn, 3.8 g / L Al, 0.2 g / L Li with a Li:M ratio of 0.01.

[0079] The leaching solution is then heated to 80 °C in a glass beaker. Once at temperature, 16.4 g of NiCO 3 and 2.7 g of CoCO 3 A stirrer is added to ensure a homogenous solution, which dissolves Ni and Co while Al is selectively precipitated out of solution. The purified filtrate contains 112 g / L Ni, 21 g / L Co, <0.05 g / L Mn, <0.05 g / L Al, and 0.2 g / L Li.

[0080] The Ni- and Co-concentrations are then corrected to obtain the desired N to Co ratio before the final crystallization of the Ni-Co mixed sulfate crystals. In this case we aim for a Ni:Co molar ratio of 6:2. This is achieved by reheating the solution in a stirred beaker at 80° C. and adding 45 g of cobalt sulfate heptahydrate crystals. 100 mL of water is also added at this stage to obtain a filtrate containing 96 g / L Ni, 32 g / L Co, <0.05 g / L Mn, <0.05 g / L Al, and 0.2 g / L Li.

[0081] Evaporative crystallization is carried out at 20°C. As a result, mixed nickel and cobalt sulfate crystals are formed. The crystals contain 17.6% Ni, 5.8% Co, <0.001% Mn, <0.001% Al, 0.001% Li. NiSO 4 6H 2 O and CoSO 4 7H 2 It is hypothesized that a mixture of Ni and O is formed, with the remainder including sulfates and water of hydration. The weight ratio of Ni to Co is 3.03, confirming the desired molar ratio.

[0082] Further aspects of the invention are provided by the subject matter of the following sections. [Section 1] 1. A method for recovering metals M, including Ni and Co, from a Li-containing starting material, comprising the steps of: Step 1: Providing starting materials comprising a lithium ion battery or a derivative thereof; Step 2: - a pyrometallurgical refining process using a slag-forming agent to produce one or more of a Li-bearing slag phase and Li fumes, and a Li-reduced Ni-Co-bearing phase that is susceptible to acid leaching; - a heat treatment process using a reducing agent to produce a Ni-Co-bearing residue containing at least one water-soluble Li-compound and to remove said at least one Li-compound by washing with an aqueous solution, thereby obtaining a Li-reduced Ni-Co-bearing residue susceptible to acid leaching; - a hydrometallurgical leaching process using aqueous or acidic solutions in which Li is leached from the starting material, Ni and Co being at least partially insoluble, and solid-liquid separation to obtain a Li-depleted Ni-Co bearing residue which is amenable to acid leaching; removing Li in excess of the maximum of: (1) 30% of the Li present in the starting material; and (2) a percentage of Li present in the starting material determined to obtain a Li:M ratio of 0.70 or less in a subsequent acid leaching step; Step 3: carrying out a subsequent leaching using relative amounts of the Li-depleted Ni-Co-bearing material obtained in step 2 and a mineral acid, thereby obtaining a Ni- and Co-bearing solution; Step 4: Crystallizing Ni, Co, and optionally Mn; A method comprising: [Section 2] 13. The method of any preceding claim, wherein the heat treating process of step 2 is carried out at a temperature greater than 250° C. [Section 3] 13. The method of any preceding claim, wherein the step of removing the at least one water-soluble Li-compound by washing with an aqueous solution is carried out at a pH of 2.5 or greater. [Section 4] The at least one water-soluble Li-compound of step 2 is Li 2 O, Li 2 CO 3 , LiHCO 3 , LiCl, Li 2 SO 4 4. The method of any preceding claim, wherein the cation exchange material comprises one or more of: LiF, LiOH. [Section 5] Mineral acid is HNO 3 , H 2 SO 4 and HCl. [Section 6] 13. The method of any preceding claim, wherein the pyrometallurgically refined Ni-Co-bearing phase of step 2 is ground to a particle size distribution having an average diameter of 10 mm or less, preferably 1 mm or less, more preferably 0.5 mm or less. [Section 7] 4. The method according to any preceding claim, wherein step 4 is carried out by reducing the temperature of the Ni- and Co-bearing solution, and / or by removing water from the Ni- and Co-bearing solution, and / or by solvent displacement crystallization. [Section 8] 13. The method of any preceding claim, wherein the Ni- and Co-bearing solution from step 3 also contains Cu and / or Fe and / or Al, and the method comprises a purification step between step 3 and step 4, in which Cu and / or Fe and / or Al are removed from the Ni- and Co-bearing solution. [Section 9] 2. The method of any preceding claim, wherein the Ni- and Co-bearing solution from step 3 also contains Mn, and the method comprises a Mn removal step between steps 3 and 4, wherein Mn is removed from the Ni- and Co-bearing solution. [Section 10] 4. The method of any preceding claim, wherein prior to step 4, the ratio of Ni to Co in the Ni- and Co-bearing solution is adjusted to a desired value by adding Ni and / or Co in dissolved form or as one or more compounds that are soluble in the Ni- and Co-bearing solution. [Section 11] 13. The method of any preceding claim, wherein prior to step 4, the ratio of Ni to Co to Mn in the Ni- and Co-bearing solution is adjusted to a desired value by adding one or more of Ni, Co, and Mn in dissolved form or as one or more compounds that are soluble in the Ni- and Co-bearing solution. [Section 12] 13. The method according to any preceding claim, wherein the Ni- and Co-bearing solution contains more Ni than Co, expressed in g / l. [Section 13] 13. The method of any preceding claim, wherein the Ni- and Co-bearing solution contains more Ni, expressed in g / l, than the sum of Co and Mn. [Section 14] 13. The method according to any preceding claim, comprising a purification step between steps 3 and 4, wherein Co is selectively removed from the Ni- and Co-bearing solution to obtain a Co-reduced Ni-bearing solution suitable for obtaining Ni crystals. [Section 15] 13. The method of any preceding claim, wherein the starting material contains Ni, Co, Li, Al, F, and one or more of Cu and Fe, and the pyrometallurgical refining process of step 2 is a reduction refining of the starting material using a flux, and the Ni-Co-bearing phase is an alloy containing most of Ni, Co, Cu and at least a portion of Fe, the alloy being depleted in Li, Al, and F.

Claims

1. A method for recovering metals M, including Ni and Co, from a Li-containing starting material, comprising the steps of: Step 1: Providing a starting material comprising a lithium ion battery or a derivative thereof; Process 2: - a pyrometallurgical refining process using a slag-forming agent to produce one or more of a Li-bearing slag phase and Li-fumes, and a Li-reduced Ni-Co-bearing phase that is susceptible to acid leaching; - hydrometallurgical leaching using aqueous or acidic solutions to leach Li from the starting material, Ni and Co being at least partially insoluble, and solid-liquid separation to obtain a Ni-Co-bearing residue with reduced Li susceptible to acid leaching; removing Li in excess of the maximum of: (1) 30% of the Li present in the starting material; and (2) a percentage of Li present in the starting material determined to obtain a Li:M ratio of 0.70 or less in a subsequent acid leaching step; Step 3: carrying out a subsequent leaching using the relative amounts of the Li-depleted Ni-Co-bearing material obtained in step 2 and a mineral acid, thereby obtaining a Ni- and Co-bearing solution; Step 4: Crystallizing Ni, Co, and optionally Mn by reducing the temperature of the Ni- and Co-bearing solution and / or by removing water from the Ni- and Co-bearing solution and / or by solvent displacement crystallization. Including, The method of claim 1, wherein the Li:M ratio is the molar concentration of Li relative to the total molar concentration of Ni+Co+Mn.

2. The mineral acid is HNO 3 , H 2 SO 4 4. The method of claim 1, wherein the at least one of the above is one or more of:

3. 3. The method according to claim 1 or 2, wherein the pyrometallurgically refined Ni-Co-bearing phase of step 2 is ground to a particle size distribution having a mean diameter of 10 mm or less.

4. 4. The method according to any one of claims 1 to 3, wherein the Ni- and Co-bearing solution from step 3 also contains Cu and / or Fe and / or Al, and the method comprises a purification step between steps 3 and 4, in which Cu and / or Fe and / or Al are removed from the Ni- and Co-bearing solution.

5. 5. The method according to any one of claims 1 to 4, wherein the Ni- and Co-bearing solution from step 3 also contains Mn, and the method comprises a Mn removal step between steps 3 and 4, in which Mn is removed from the Ni- and Co-bearing solution.

6. 6. The method according to any one of claims 1 to 5, wherein prior to step 4, the ratio of Ni to Co in the Ni- and Co-bearing solution is adjusted to a desired value by adding Ni and / or Co in dissolved form or as one or more compounds that are soluble in the Ni- and Co-bearing solution.

7. 7. The method according to any one of claims 1 to 6, wherein prior to step 4, the ratio of Ni to Co to Mn in the Ni- and Co-bearing solution is adjusted to a desired value by adding one or more of Ni, Co, and Mn in dissolved form or as one or more compounds that are soluble in the Ni- and Co-bearing solution.

8. 8. The method according to claim 1, wherein the Ni- and Co-bearing solution contains more Ni than Co, expressed in g / l.

9. 9. The method according to any one of claims 1 to 8, wherein the Ni- and Co-bearing solution contains more Ni, expressed in g / l, than the sum of Co and Mn.

10. 10. The method according to any one of claims 1 to 9, comprising a purification step between steps 3 and 4, in which Co is selectively removed from the Ni- and Co-bearing solution to obtain a Co-reduced Ni-bearing solution suitable for obtaining Ni crystals.

11. 11. The method of any one of claims 1 to 10, wherein the starting material contains one or more of Ni, Co, Li, Al, F, and Cu and Fe, and the pyrometallurgical refining process of step 2 is a reduction refining of the starting material using a flux, and the Ni-Co-bearing phase is an alloy comprising most of Ni, Co, Cu and at least a portion of Fe, the alloy being depleted in Li, Al, and F.

Citation Information

Patent Citations

  • Method for recycling lithium, nickel, cobalt and manganese from waste ternary anode material

    CN107666022A

  • Method for recovering valuable metal

    JP2002339023A

  • Method for recovering valuable metal

    JP2012224877A

  • Method for separating and recovering valuable material from used lithium ion battery

    JP2012229481A

  • Methods for recycling metals contained in lithium-ion batteries

    JP2013506048A